2007
DOI: 10.1016/s0301-0546(07)70227-6
|View full text |Cite
|
Sign up to set email alerts
|

Polysensitization to aeroallergens and food in eosinophilic esophagitis in a pediatric population

Abstract: There are few studies on eosinophilic esophagitis (EE) in the pediatric population in Europe. We present our data and emphasize the following findings: a) all patients had symptoms of allergic respiratory disease prior to receiving a diagnosis of EE with polysensitization (aeroallergens, food allergens); and b) in contrast with the results of earlier studies, food sensitization in our series most often corresponded to legumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 8 publications
2
7
0
3
Order By: Relevance
“…In order to maintain a large pool of patients in the subcohort, we also did not attempt to match the subcohort to the general EoE population for age and gender. In our study, 44.7% patients had AR, 27.1% had asthma, 25.2% had AD, and 16.9% had food allergies, which was comparable to rates reported in the published literature . The results from our study are therefore aligned with overall published estimates and confirm a greater‐than‐average prevalence of asthma, AR, and food allergies in patients with EoE, as the overall U.S. prevalence of these conditions was estimated at 14%, 10%, and 8.9%, respectively …”
Section: Discussionsupporting
confidence: 90%
“…In order to maintain a large pool of patients in the subcohort, we also did not attempt to match the subcohort to the general EoE population for age and gender. In our study, 44.7% patients had AR, 27.1% had asthma, 25.2% had AD, and 16.9% had food allergies, which was comparable to rates reported in the published literature . The results from our study are therefore aligned with overall published estimates and confirm a greater‐than‐average prevalence of asthma, AR, and food allergies in patients with EoE, as the overall U.S. prevalence of these conditions was estimated at 14%, 10%, and 8.9%, respectively …”
Section: Discussionsupporting
confidence: 90%
“…For example, in an initial case report highlighting this association, a patient’s esophageal eosinophil count was markedly increased during pollen seasons and normalized when the pollen was not present (42). Since then, larger studies have confirmed a relationship between aeroallergens and eosinophilic esophagitis in humans (41, 43), a relationship that has been established as causal in a murine model of EoE (44, 45). Seasonal variation has also been reported in multiple studies of EoE, a pattern that also argues for possible environmental triggers (6, 9, 40, 41, 46, 47).…”
Section: Discussionmentioning
confidence: 94%
“…Interesting data from Plaza-Martín et al [35] emphasized that all patients with EE have symptoms of allergic respiratory disease prior to receiving a diagnosis of EE with poly-sensitization (aeroallergens and food allergens): food sensitization in this series most often corresponded to legumes, which have a cross-reaction with pollens.…”
Section: Dietary Intervention In Eosinophilic Esophagitismentioning
confidence: 87%